2005
DOI: 10.21273/jashs.130.2.232
|View full text |Cite
|
Sign up to set email alerts
|

Expression of α-Farnesene Synthase AFS1 and 3-Hydroxy-3-methylglutaryl-coenzyme A Reductase HMG2 and HMG3 in Relation to α-Farnesene and Conjugated Trienols in `Granny Smith' Apples Heat or 1-MCP Treated to Prevent Superficial Scald

Abstract: Untreated control, 1-methylcyclopropene (1-MCP)-treated, and heated fruit of the superficial scald-susceptible `Granny Smith' cultivar of apple [Malus sylvestris (L.) Mill. var. domestica (Borkh.) Mansf.] were compared with respect to scald incidence, internal ethylene concentration (IEC), α-farnesene metabolism, expression of the genes AFS1, which encodes α-farnesene synthase, the final, rate-limiting enzyme in the α-farn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
30
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 34 publications
8
30
0
Order By: Relevance
“…The effect of AA in inhibiting ethylene production has been shown in several other fruits, including grape, tomato, mango, avocado and banana 17. It is well known that ethylene mediates the synthesis of α‐farnesene, leading to scald symptoms,5, 6 and that application of 1‐MCP, an ethylene action inhibitor, prevents scald development in apples 3, 7–12. Also in our research, application of 1‐MCP was the most effective at reducing ethylene production, leading to lower scald development.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The effect of AA in inhibiting ethylene production has been shown in several other fruits, including grape, tomato, mango, avocado and banana 17. It is well known that ethylene mediates the synthesis of α‐farnesene, leading to scald symptoms,5, 6 and that application of 1‐MCP, an ethylene action inhibitor, prevents scald development in apples 3, 7–12. Also in our research, application of 1‐MCP was the most effective at reducing ethylene production, leading to lower scald development.…”
Section: Discussionsupporting
confidence: 69%
“…The development of scald is caused by autoxidation products of α‐farnesene, identified as conjugated trienes and 6‐methyl‐5‐hepten‐2‐one, in apple skin 4. Several studies have shown that the synthesis of α‐farnesene is mediated by ethylene,5, 6 and in recent years many studies have demonstrated that the ethylene action inhibitor 1‐methylcyclopropene (1‐MCP) is very powerful at preventing scald in apples, which again confirms that ethylene is the main inducer of scald development 3, 7–12…”
Section: Introductionmentioning
confidence: 82%
“…According to other references [[16],[19],[20],[33]] α-farnesene was linearly accumulated after the first month of cold storage and in particular during the first period of room temperature shelf life, with a clear increase from the T1 +1 to T1 +8 stages, after which a more constant profile was observed during T2 shelf life (Figure 4B). The burst in this volatile was positively correlated with the activation and transcription dynamics of MdAFS1 , the gene designated to encoding the last step of the α-farnesene synthesis (Figure 4A).…”
Section: Resultssupporting
confidence: 61%
“…In apples, ethylene is known to play a key role in the development of superficial scald since this hormone is involved in the synthesis of ␣-farnesene by regulating gene expression of hydroxymethylglutaryl-CoA reductase (HMGR) and/or ␣-farnesene synthase (Ju and Curry, 2000). Accordingly, scaldsusceptible pears and apples typically exhibit higher rate of ␣-farnesene (AF) than resistant fruit, shortly after they are placed in low temperature storage (Huelin and Coggiola, 1970;Whitaker et al, 1997;Lurie et al, 2005;Gapper et al, 2006;Giné Bordonaba et al, 2013).…”
Section: Introductionmentioning
confidence: 99%